2017
DOI: 10.6113/jpe.2017.17.3.610
|View full text |Cite
|
Sign up to set email alerts
|

Modified Finite Control Set-Model Predictive Controller (MFCS-MPC) for quasi Z-Source Inverters based on a Current Observer

Abstract: The Finite Control Set-Model Predictive Controller (FCS-MPC) for quasi Z-Source Inverters (qZSIs) is designed to reduce the number of sensors by proposing a current observer for the inductor current. Unlike the traditional FCS-MPC algorithm, the proposed model removes the inductor current sensor and observes the inductor current value based on the deposited prior optimized state as well as the capacitor voltage during this state. The proposed observer has been validated versus a typical MPC. Then, a comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The three-phase voltage source inverter (VSI) can connect the three-phase load to the positive or negative terminals of the DC link (V dc ) by using different combinations of their switches. However, qZSI has an extra state in addition to the eight states, which is a shoot-through state [33]. This study proposes a modified model predictive controller (MMPC) as shown in Fig.…”
Section: Modified Model Predictive Control (Mmpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The three-phase voltage source inverter (VSI) can connect the three-phase load to the positive or negative terminals of the DC link (V dc ) by using different combinations of their switches. However, qZSI has an extra state in addition to the eight states, which is a shoot-through state [33]. This study proposes a modified model predictive controller (MMPC) as shown in Fig.…”
Section: Modified Model Predictive Control (Mmpc)mentioning
confidence: 99%
“…This study has modified a model predictive control (MPC) algorithm [33], that was used to control a three-phase quasi Z-source inverter (qZSI) by providing the switching states of the inverter. The original MPC algorithm aimed to minimize the total harmonic distortion (THD) of the output currents without considering the inverter power losses.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of hysteresis comparators for power control generates high-power ripples and variable switching frequency, which increase the power losses and produces an unexpected wide band gap harmonic spectrum range, which implies that designing a line filter is difficult. Model predictive control (MPC) has become a popular technique for power converters in the last decade due to its simplicity, flexibility, and ease of adding control limitations [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when the system parameters are not well designed, a complex bifurcation phenomenon may occur [19][20][21][22] and cause the system performance degradation or even lead to instability [20,21]. Because of the simplicity, flexibility, discrete nature, and inherent adaptation to the power electronic circuits, model predictive control (MPC) is also gradually utilized in the power converters [23][24][25][26]. The dynamic phasor model-based model predictive control DAB converter is obtained in Reference [27].…”
Section: Introductionmentioning
confidence: 99%